IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF KRITIS UNTUK MENINGKATKAN KUALITAS PRODUK PEMIKIRAN TULIS PADA MATAKULIAH PUISI - Arti Prihatini,; Candra Rahma Wijaya Putra,; Hari Sunaryo, (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
This program aims to describe the implementation of the critical-cooperative learning model to improve the quality of written thinking products in the Poetry course. This program had an implementation of lesson study in four cycles. The data described the implementation process of the critical cooperative learning model to improve the quality of written thinking products and the results of students' written thinking products. The targets of this program were Indonesian Language Education students at Universitas Muhammadiyah Malang in the Poetry Course. Data collection is held by documentation and observation. Data analysis was carried out in several stages, namely (1) analyzing the learning process, (2) analyzing student activities, and (3) analyzing the results of the implementation of the critical cooperative learning model. This program found that the critical cooperative model successfully improved the quality of written thinking products in the form of popular articles and scientific articles. This result could be identified by the writing process carried out by students and the results of writing that students have revised. Cooperative learning was carried out through peer review and discussion activities. Students also improved their writing and critical thinking skills when compiling ideas in their articles. In the writing process of scientific papers, students also needed to be critical in relating the discussion to the theory and results of previous research. In the writing process of popular articles, students develop logical and critical arguments based on actual and factual phenomena in society. Critical thinking was not only limited to writing papers but also the peer review process. --- Program ini bertujuan mendeskripsikan implementasi model pembelajaran kooperatif kritis untuk meningkatkan kualitas produk pemikiran tulis pada matakuliah Puisi. Program ini merupakan implementasi lesson study dalam empat siklus. Data berupa deskripsi proses implementasi model pembelajaran kooperatif kritis untuk meningkatkan kualitas produk pemikiran tulis dan hasil produk pemikiran tulis karya mahasiswa. Sasaran kegiatan ini adalah mahasiswa Pendidikan Bahasa Indonesia Universitas Malang pada Matakuliah Puisi. Pengumpulan data dilakukan dengan dokumentasi dan observasi. Analisis data dilaksanakan dalam beberapa tahap, yaitu (1) menganalisis proses pembelajaran, (2) menganalisis aktivitas peserta didik, (3) menganalisis hasil implementasi model pembelajaran kooperatif kritis. Hasil kegiatan menunjukkan bahwa model kooperatif kritis berhasil dalam meningkatkan kualitas produk pemikiran tulis berupa artikel popular dan artikel ilmiah. Hal itu tampak dari proses penulisan yang dilakukan oleh mahasiswa dan hasil tulisan yang telah melalui revisi. Pembelajaran kooperatif dilaksanakan dalam bentuk kegiatan peer review dan diskusi. Mahasiswa juga menunjukkan peningkatan keterampilan dalam penulisan dan kemampuan berpikir kritis ketika menyusun gagasan-gagasan dalam artikel yang ditulisnya. Pada penulisan artikel ilmiah, mahasiswa juga perlu kritis dalam mengaitkan pembahasan dengan teori dan hasil penelitian sebelumnya. Pada penulisan artikel popular, mahasiswa mengembangkan argumen logis dan kritis berdasarkan fenomena actual dan faktual yang terjadi di masyarakat. Berpikir kritis tidak hanya terbatas pada penulisan artikel, melainkan juga proses mereview karya mahasiswa lain.